Transformation of Cardiac Intensive Care Wards Into Cardiac Resuscitation Department. The Five-year Evolution - M. F. Mukhamadeev; E. S. Dumanyan; R. A. Yakubov; B. Z. Zagidullin; G. M. Khayrutdinova (Неотложная медицинская помощь, 2023)
The article highlights the key elements and results of the restructuring of emergency care for patients with acute myocardial infarction, the core of which is the teamwork of surgeons, anesthesiologist-intensivists and cardiologists of the department. The restructuring included a change in ideology, personnel changes, updating and expanding the range of equipment, development of inner protocols and their implementation. It took two years to transform the intensive care unit for patients with acute myocardial infarction into the cardiac intensive care unit, where patients with acute cardiac pathologies of various etiologies are treated and preoperative preparation and postoperative nursing are carried out.